2019
DOI: 10.1017/s1368980019002301
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting safe and healthy diet in older adults in Italy: results of a preliminary study performed in a community-dwelling sample

Abstract: Objective:To investigate, through a questionnaire, older adults’ demographic and socio-economic characteristics, knowledge, attitudes and practices in terms of food safety and healthy diet; and to develop dietary and hygiene indices able to represent participants’ nutritional and food safety behaviour, exploring their association with demographic and socio-economic factors.Design:One-year cross-sectional study.Setting:Gemelli Teaching Hospital (Rome, Italy).Participants:People aged ≥65 years, Italian speaking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…49 Thus, some risk-averse attitudes might represent overreactions. 50 Risk perceptions are dependent on previous experiences. 51 Risk perceptions and related factors can influence individual's healthcare-seeking behaviour in many ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Thus, some risk-averse attitudes might represent overreactions. 50 Risk perceptions are dependent on previous experiences. 51 Risk perceptions and related factors can influence individual's healthcare-seeking behaviour in many ways.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, risk perceptions might be incorrect, as online health information can be incorrect or misunderstood 49 . Thus, some risk‐averse attitudes might represent overreactions 50 …”
Section: Discussionmentioning
confidence: 99%
“…A related study also showed that older adults with lower diet-related knowledge tend to have poorer practices related to diet [ 26 ]. Overall, older adults often have insufficient knowledge regarding healthy diets, especially when compared with younger individuals [ 27 , 28 ]. Having higher levels of knowledge and more positive attitudes toward a healthy diet are associated with positive diet behaviors, including increased consumption of fruits and vegetables and actively seeking out nutritional information [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge, attitude, and behavioral intention are important variables in psychological research on human health-related behaviors. Studies of the elderly have found that improving the knowledge of healthy diet and food safety in the elderly helps promote the behavior of healthy diet [16] . The higher the knowledge and attitude of the elderly regarding tetanus, pneumococcal, and influenza vaccination, the higher the behavior of vaccination against tetanus, pneumococcal, and influenza vaccine [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the elderly have found that improving the knowledge of healthy diet and food safety in the elderly helps promote the behavior of healthy diet. [16] The higher the Editor: Daryle Wane.…”
Section: Introductionmentioning
confidence: 99%